Racism in Mississippi Burning Film - Nugroho, Wulan Indri Safitri (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
The purpose of this research is to reveal what happened toward black people in Mississippi in 19th century, the researcher used qualitative research and mimetic approach to analyse this research. The researcher used Jones theory about levels of racism and effects of racism. The researcher found there are three levels of racism in the film: institutionalized racism, personally mediated racism and internalized racism. And the researcher also found positive and negative effects of racism, positive effect: motivation and feeling responsible and negative effects: disfavour society and violence. Yet, inferiority complex is not found in this research. This research is expected to provide deeper understanding to the readers about racial issue and this research will also raise awareness about racial issue.